Assessing the importance of four sandfly species (Diptera: Psychodidae) as vectors of Leishmania mexicana in Campeche, Mexico - Pech May, Angélica del Rosario (2016)
Localized cutaneous leishmaniasis represents a public health problem in many areas of Mexico, especially in the Yucatan Peninsula. An understanding of vector ecology and bionomics is of great importance in evaluations of the transmission dynamics of Leishmania parasites. A field study was conducted in the county of Calakmul, state of Campeche, during the period from November 2006 to March 2007. Phlebotomine sandfly vectors were sampled using Centers for Disease Control light traps, baited Disney traps and Shannon traps. A total of 3374 specimens were captured in the two villages of Once de Mayo (93.8%) and Arroyo Negro (6.1%). In Once de Mayo, the most abundant species were Psathyromyia shannoni, Lutzomyia cruciata, Bichromomyia olmeca olmeca and Psychodopygus panamensis (all: Diptera: Psychodidae). The Shannon trap was by far the most efficient method of collection. The infection rate, as determined by Leishmania mexicana-specific polymerase chain reaction, was 0.3% in Once de Mayo and infected sandflies included Psy. panamensis, B. o. olmeca and Psa. shannoni. There were significant differences in human biting rates across sandfly species and month of sampling. Ecological niche modelling analyses showed an overall overlap of 39.1% for the four species in the whole state of Campeche. In addition, the finding of nine vector-reservoir pairs indicates a potential interaction. The roles of the various sandfly vectors in Calakmul are discussed.